Metabolome and gut microbiota variation with long-term intake of Panax ginseng extracts on rats. Issue 6 (13th June 2018) - Sun, Yifan; Chen, Shaoqiu; Wei, Runmin; Xie, Xie; Wang, Chongchong; Fan, Shihao; Zhang, Xia; Su, Juan; Liu, Jiajian; Jia, Wei; Wang, Xiaoyan
Abstract : In this study, untargeted GC-TOFMS metabolomic analysis of serum, cecum and ileum intestinal contents was conducted to understand the effect of the long-term intake of Ginseng extracts. Abstract : Ginseng, a widely used functional food and food additive, has been proven to have promotion effects of health on the body. However, whether the long-term intake of Ginseng is beneficial or has side effects on an organism is still unclear. In this study, untargeted GC-TOFMS metabolomic analysis of serum, cecum and ileum intestinal contents was conducted to understand the effect of the long-term intake of Ginseng extracts. 16S rRNA microbial sequencing technology was applied to investigate the effect of Ginseng extracts on the structure of gut microbiota. Cytokines in spleen were detected to determine the effect of Ginseng extracts on the immune system. Compared to control groups, the metabolites in serum, cecum and ileum, such as amino acids, amines and other metabolites related to carbohydrate metabolism, significantly varied between the C and GS groups. Ginseng extracts affected the structure of gut microbiota with a decreased abundance of TM7, while the abundance of Proteobacteria, Methylobacteriaceae, Parasutterella, Sutterella increased in the GS group. The increased abundance of Bifidobacterium and Lactobacillus demonstrated that Ginseng extracts contribute to probiotic amplification. Highly correlated with Bifidobacterium and Lactobacillus, interleukin 4 (IL4), IL10 and immunoglobulin A (IgA) levels were significantly elevated after the long-term intake of Ginseng extracts. These results indicated that the long-term administration of Ginseng extracts positively affected the host-gut metabolism, immune system, the anti-inflammation process and the gut intestinal microbiota structure.